1977
DOI: 10.1111/j.1432-1033.1977.tb11256.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Translation in Eukaryotic Systems by Harringtonine

Abstract: The Cephalotaxus alkaloids harringtonine, homoharringtonine and isoharringtonine inhibit protein synthesis in eukaryotic cells. The alkaloids do not inhibit, in model systems, any of the steps of the initiation process but block poly(U)-directed polyphenylalanine synthesis as well as peptide bond formation in the fragment reaction assay, the sparsomycin-induced binding of (C)U-A-C-C-ArH]Leu-Ac, and the enzymic and the non-enzymic binding of Phe-tRNA to ribosomes. These results suggest that the Cephalotaxus alk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
177
0
1

Year Published

1989
1989
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(182 citation statements)
references
References 20 publications
(5 reference statements)
3
177
0
1
Order By: Relevance
“…HHT has been found to inhibit the elongation phase of translation by preventing substrate binding to the acceptor site on the 60S ribosome subunit (41,42). As expected, HHT dramatically decreased KIT level and inhibited the growth of MCL cells, including D816V-bearing cells.…”
Section: Discussionmentioning
confidence: 72%
“…HHT has been found to inhibit the elongation phase of translation by preventing substrate binding to the acceptor site on the 60S ribosome subunit (41,42). As expected, HHT dramatically decreased KIT level and inhibited the growth of MCL cells, including D816V-bearing cells.…”
Section: Discussionmentioning
confidence: 72%
“…It has been initially proposed that these compounds inhibit initiation in intact cells and cell lysates [ 1,2]. Further investigations clearly showed that such an effect was due to the prevention of the elongation cycle in contradiction to the previous proposals [3,4]. The results presented in the above-mentioned works suggested that Cephalotaxus alkaloids inhibited not only peptide bond formation in the fragment reaction assays but also enzymatic and non-enzymatic binding of the PhetRNAPhe to ribosomes.…”
Section: Homoharringtonine and Related Alkaloids Frommentioning
confidence: 93%
“…According to [3], Cephalotuxus alkaloids prevent not only transpeptidation but also tRNA binding to ribosomes (both nonenzymatic and enzymatic). Probably, the mechanism of the alkaloids' inhibitory action depends on the source of ribosomes.…”
Section: Homoharringtonine and Related Alkaloids Frommentioning
confidence: 99%
“…11,12 In fact, its cytotoxicity has been shown to be proportional to the extent of inhibition of protein synthesis. 13,14 HHT has been shown to induce apoptosis in vitro, however, the main components of HHT-induced apoptotic pathway remain to be identified. 12,15 In the present study we investigated cell death induced by HHT in human leukemic cells.…”
Section: Introductionmentioning
confidence: 99%